Adolescents' views on oral health care and promotion in Norway: everyday practices, recommendations, and future visions - Høiseth, Marikken; Jasbi, Arefe (Frontiers in Oral Health, 2024)
Introduction In this study, we aimed to understand adolescents' perspectives on oral health care and promotion. Our research was conducted in the context of Norway's oral health care system, where societal factors like income and education influence health disparities. Despite free public dental care for all residents younger than 19 years, challenges persist in promoting oral health among adolescents, a group whose oral health behavior and literacy remain largely unexplored. Materials and methods A thematic analysis of an anonymized dataset from 80 adolescents aged 12–20 years was conducted. Results Five central themes were recognized: (1) Feeling fresh vs. feeling indifferent: A broad spectrum of attitudes; (2) Bridging gaps, building habits: Collaborative efforts in oral care; (3) “Create good experiences at the dentist so people come back again”; (4) Requested qualities in oral health promoting solutions; (5) Reminder tools for everyday use. Taken together, these themes highlight adolescents' oral health practices and resources, recommendations for dental clinics, and visions for future oral health promotion. Discussion Based on the results, the discussion highlights a need for tailored oral health promotion and ideas to reach adolescents in meaningful and effective ways. Reflections on the theme of social inequalities are provided.